BUNYI / / DAN //: KARAKTERISTIK BAHASA BONAI ULAK PATIAN - Zainal Abidin (Madah: Jurnal Bahasa dan Sastra, 2015)
The research regarding the phonology of  Bonai language  has not much done. This causes lack of knowledge about the characteristic of Bonai language, especially Ulak Patian, dialect. Hence, it is important to do the research that aim to describe the specific characteristic of  Bonai Language, Ulak Patian dialect. By applying descriptive qualitative method, the data  of  utterances of  the remote indigenous  community of Bonai was collected by using conversation and listen method. The technique used is is recording and taking notes.. After recording and taking notes, the data was analyzed by  making classification, transcription and conclusion. The result of this research shows that the retroplex sounds / /, //, and /g/ are the characteristic of bahasa Bonai, Ulak Patian dialect as the variation of the sound  /t/ dan /n/, /k/, dan /!/ Pasang Padang and Bonai dialects.